Aggregation chimeras provide evidence of in vivo intercellular correction in ovine CLN6 neuronal ceroid lipofuscinosis (Batten disease). - Lucy Anne Barry (PLoS ONE, 2022)
The neuronal ceroid lipofuscinoses (NCLs; Batten disease) are fatal, mainly childhood, inherited neurodegenerative lysosomal storage diseases. Sheep affected with a CLN6 form display progressive regionally defined glial activation and subsequent neurodegeneration, indicating that neuroinflammation may be causative of pathogenesis. In this study, aggregation chimeras were generated from homozygous unaffected normal and CLN6 affected sheep embryos, resulting in seven chimeric animals with varied proportions of normal to affected cells. These sheep were classified as affected-like, recovering-like or normal-like, based on their cell-genotype ratios and their clinical and neuropathological profiles. Neuropathological examination of the affected-like animals revealed intense glial activation, prominent storage body accumulation and severe neurodegeneration within all cortical brain regions, along with vision loss and decreasing intracranial volumes and cortical thicknesses consistent with ovine CLN6 disease. In contrast, intercellular communication affecting pathology was evident at both the gross and histological level in the normal-like and recovering-like chimeras, resulting in a lack of glial activation and rare storage body accumulation in only a few cells. Initial intracranial volumes of the recovering-like chimeras were below normal but progressively recovered to about normal by two years of age. All had normal cortical thicknesses, and none went blind. Extended neurogenesis was evident in the brains of all the chimeras. This study indicates that although CLN6 is a membrane bound protein, the consequent defect is not cell intrinsic. The lack of glial activation and inflammatory responses in the normal-like and recovering-like chimeras indicate that newly generated cells are borne into a microenvironment conducive to maturation and survival.